Spiritual Pedagogic Foundation: Analysis of Western and Islamic Sociological Theory - Gita Dianita; Aam Abdussalam (Islamic Research, 2020)
This research was conducted to review various problems in education and solutions in dealing with them. This research aims to explore Islamic and western sociological theories as a basis for spiritual pedagogic development. This study uses a qualitative approach and literature study methods. The results of this study indicate that Islam pays special attention to human potential as social beings. In the Quran, there are three sociological concepts, namely tadafu, ta'aruf, and ta'awun. The three of them are the foundation that strengthens that humans have a natural tendency to defend the truth and oppose evil, and live amid the diversity of characteristics of fellow humans. With various studies on sociology, inclusive Islamic education needs to be applied to foster students in caring for their relationship with God and with fellow humans. Thus, religion plays a role as a solution amid human life to form a civil society, promoting monotheism values ​​in its social interactions.